Aplikasi Intenet of Things Pada Rumah Pintar Berbasis Android: Internet of Things Applications in Android-Based Smart Homes - Daniel Runtu; Pinrolivic Manembu; Xaverius Najoan (Jurnal Teknik Informatika, 2025)
The advancement of technology has significantly impacted daily life by incorporating Internet of Things (IoT) and voice-based personal assistants. However, the complexity of using personal assistants to control household electronic devices has increased alongside IoT advancements. The surge in electricity consumption due to modern lifestyles also presents a challenge. In this context, this research proposes the development of an Android application utilizing IoT to control household electronic devices automatically or remotely. This application also provides electricity usage prediction, enabling users to optimize their energy consumption. Thus, this application is expected to assist users in reducing electricity bills and mitigating the environmental impact of excessive electricity production.